2008
DOI: 10.1111/j.1365-3040.2008.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific responses of Populus cathayana to drought and elevated temperatures

Abstract: Dioecious plant species represent an important component of terrestrial ecosystems. Yet, little is known about sexspecific responses to drought and elevated temperatures. Populus cathayana Rehd, which is a dioecious, deciduous tree species, widely distributed in the northern, central and southwestern regions of China, was employed as a model species in our study. In closed-top chamber experiments, sex-specific morphological, physiological and biochemical responses of P. cathayana to drought and different eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
119
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 61 publications
20
119
1
3
Order By: Relevance
“…Females are generally more prone to sexual spatial segregation and more abundant in moist and resource-rich environments (Freeman et al 1976;Rowland and Johnson 2001;Hultine et al 2007). Sex niche partitioning results from the different tolerance levels to harsh stress (Xu et al 2008;Zhang et al 2010;Montesinos et al 2012) and different resource demands, such as water, light, and temperature (Dawson et al 2004;Li et al 2007;Xu et al 2008;Zhao et al 2009;Zhang et al 2010). The preference for different N forms may have a function in special segregation of the sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Females are generally more prone to sexual spatial segregation and more abundant in moist and resource-rich environments (Freeman et al 1976;Rowland and Johnson 2001;Hultine et al 2007). Sex niche partitioning results from the different tolerance levels to harsh stress (Xu et al 2008;Zhang et al 2010;Montesinos et al 2012) and different resource demands, such as water, light, and temperature (Dawson et al 2004;Li et al 2007;Xu et al 2008;Zhao et al 2009;Zhang et al 2010). The preference for different N forms may have a function in special segregation of the sexes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, elevated temperature is an essential mediator in plant photosynthesis and chlorophyll contents. A previous study has showed that elevated temperature stimulates the photosynthesis rate, light saturated rate of CO 2 uptake (A sat ) and U in Populus cathayana (Xu et al 2008). It has been thought that an increase in the photosynthesis rate of three Mediterranean pine species caused by elevated temperature results from a significant increase in chlorophyll contents and U (Awada et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The computer-controlled heating and cooling system (LT/ WSK-PLC, BQHGCT Co. Led., Beijing, China), together with a set of magnetoelectric valves to control the pure CO 2 supply (pure CO 2 was produced by separating air), enabled the temperature and CO 2 concentration to be adjusted automatically inside the chambers according to the ambient conditions (Xu et al 2008).…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Stomata closure and photoinhibitory damage are considered as the major factors responsible for the depression of assimilation rate (Muraoka et al 2000). Xu et al (2008) demonstrated that drought treatment of Populus cathayana Rehd. juveniles (cuttings) had significant negative effect on their growth and net photosynthesis rate, and increased WUEi and malondialdehyde (MDA) content.…”
Section: Discussionmentioning
confidence: 99%